2014
DOI: 10.1118/1.4881519
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of volumetric noise and resolution performance for linear and nonlinear CT reconstruction methods

Abstract: A methodology was developed to measure three-dimensional CT noise and resolution properties for iterative reconstruction, especially at challenging measurement conditions with low contrast and high image noise. The methodology also demonstrated its utility for evaluating commercial CT systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 35 publications
2
101
0
Order By: Relevance
“…This choice was determined by manual tuning to obtain appropriate spectral smoothness, and is the same as that reported in a similar study (21) . In practice, the magnitude of the NPS at the spatial frequency origin false(normalfx=normalfy=0false) is difficult to estimate accurately for finite data, as has been reported in previous literature (23) . Since the radial, 1D NPS varies linearly at low spatial frequencies, (4) the zero‐frequency value of the 1D NPS in this study was estimated via linear extrapolation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This choice was determined by manual tuning to obtain appropriate spectral smoothness, and is the same as that reported in a similar study (21) . In practice, the magnitude of the NPS at the spatial frequency origin false(normalfx=normalfy=0false) is difficult to estimate accurately for finite data, as has been reported in previous literature (23) . Since the radial, 1D NPS varies linearly at low spatial frequencies, (4) the zero‐frequency value of the 1D NPS in this study was estimated via linear extrapolation.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have utilized various square ROI sizes, with side lengths of 128 pixels, 4 , 21 , 22 64 pixels, (23) and 32 pixels (19) . Similarly, multiple background removal methods have been proposed and implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this, our study focused on how size affects image quality with different imaging parameters using a second generation dual source CT scanner (SOMATOM Definition Flash, Siemens Healthcare). Some studies have reported the image quality from this new CT [5,11,13] . However, these studies focused on one particular technique, such as varying tube voltage, varying mAs, or comparing reconstruction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Lower tube voltage can provide better contrast because iodine preferentially absorbs much more photons at low tube voltage, but at lower tube voltage, images can be undesirably noisy [8][9][10][11] . Iterative reconstructions have been proven to reduce radiation dose notably, but can also alter the noise texture and obscure potential lesions of interest against a "waxy appearance" [5,7,11,12] . To optimize protocols, these tradeoffs should be carefully and conjunctively considered.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation